Prolonged Suppression of Butyrate-Producing Bacteria Is Associated With Acute Gastrointestinal Graft-vs-Host Disease and Transplantation-Related Mortality After Allogeneic Stem Cell Transplantation. (27th May 2021) - Meedt, Elisabeth; Hiergeist, Andreas; Gessner, André; Dettmer, Katja; Liebisch, Gerhard; Ghimire, Sakhila; Poeck, Hendrik; Edinger, Matthias; Wolff, Daniel; Herr, Wolfgang; Holler, Ernst; Weber, Daniela
Abstract: Background: Butyrogenic bacteria play an important role in gut microbiome homeostasis and intestinal epithelial integrity. Previous studies have demonstrated an association between administration of short-chain fatty acids like butyrate and protection from acute graft-vs-host disease (GvHD) after allogeneic stem cell transplantation (ASCT). Methods: In the current study, we examined the abundance and butyrogenic capacity of butyrate-producing bacteria in 28 healthy donors and 201 patients after ASCT. We prospectively collected serial stool samples and performed polymerase chain reaction analysis of the butyrate-producing bacterial enzyme butyryl–coenzyme A (CoA):acetate CoA-transferase (BCoAT) in fecal nucleic acid extracts. Results: Our data demonstrate a strong and prolonged suppression of butyrogenic bacteria early in the course of ASCT. In a multivariable analysis, early use of broad-spectrum antibiotics before day 0 (day of transplantation) was identified as an independent factor associated with low BCoAT copy numbers (odds ratio, 0.370 [95% confidence interval, .175–.783]; P = .009). Diminished butyrogens correlated with other biomarkers of microbial diversity, such as low 3-indoxylsulfate levels, reduced abundance of Clostridiales and low inverse Simpson and effective Shannon indices (all P < .001). Low BCoAT copy numbers at GvHD-onset were correlated with GI-GvHD severity ( P = .002) and associated with a significantly higher GvHD-associated mortality rate ( P = .04). Furthermore, low BCoAT copy numbers at day 30 were associated with a significantly higher transplantation-related mortality rate ( P = .02). Conclusions: Our results are consistent with the hypothesis that alterations in the microbiome play an important role in GvHD pathogenesis and that microbial parameters such as BCoAT might serve as biomarkers to identify patients at high risk of lethal GI-GvHD. Abstract : Butyrogenic commensals diminish early after allogeneic stem cell transplantation. This is significant because bacterial metabolites such as butyrate have important anti-inflammatory functions and stabilizing effects on gut epithelial integrity. Accordingly, loss of butyrogenic bacteria is associated with increased severity of graft-vs-host disease and increased transplantation-related mortality.